PERBANDINGAN TAFSIR AYAT MAISIR DALAM AL-AZHAR KARYA BUYA HAMKA DAN AL-MISBAH KARYA QURAISH SHIHAB: IMPLIKASI SOSIAL DAN MORAL TERHADAP PERILAKU GENERASI MUDA DI INDONESIA - Muhammad Arif Saman; Hery Sahputra (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study investigates the interpretation of maisir (gambling) as discussed in Surah Al-Baqarah [2]:219 and Al-Mā’idah [5]:90, by comparing two prominent works of contemporary Qur’anic exegesis: Tafsir al-Azhar by Buya Hamka and Tafsir al-Misbah by M. Quraish Shihab. Employing a qualitative, conceptual analysis through textual study, this research seeks to delineate the methodological differences in understanding the prohibition of gambling. Buya Hamka adopts a normative-exegetical approach, firmly emphasizing the moral and social corruption caused by all forms of maisir. In contrast, Quraish Shihab offers a contextualized hermeneutic, linking the prohibition to broader socio-economic dynamics within modern society. This paper further explores the pedagogical implications of integrating both interpretive frameworks within religious education curricula to enhance the moral awareness of Indonesian youth regarding the risks of gambling, particularly in its digital manifestations. The findings suggest that thematically integrated exegesis within religious instruction can serve as a constructive educational strategy to address contemporary moral challenges such as the rise of online gambling